Does bronchial asthma influence dental health of the diseased children? - Davidović, Bojana; Ivanović, Mirjana; Bokonjić, Dejan; Janković, Svjetlana; Erić, Jelena; Lečić, Jelena; Jovičić, Olivera (Vojnosanitetski pregled, 2022)
Background/Aim. Asthma is a chronic inflammatory lung disorder. The effect of asthma drugs on oral health is still the subject of debate among researchers in dentistry. The aim of this study was to evaluate dental status in asthmatic children and evaluate the possible effect of drugs treating asthma on dental health. Methods. Study participants were divided into two groups: the asthma (AG) and the non-asthma (NAG) group. Based on the symptoms of asthma and the possibility for effective control of the disease, the AG group was divided into two subgroups. The oral examination of the teeth was performed using a probe and mouth mirror under artificial light in accordance with the recommendations of the World Health Organization. Saliva analysis was carried out by the GC Saliva-Check Buffer, according to the manufacturer’s instructions. Results. The study included 136 children aged 6 to 16 years (10.5 ± 3.3). The mean of decayed, missing, and filled teeth (dmft/DMFT) of the children in the AG group (6.0 ± 4.0/3.3 ± 4.4) was higher than in the NAG group (4.8 ± 4.4/2.5 ± 3.4), but significant differences were not observed between the groups. Salivary pH values were found to be similar in both groups, but the quantity and buffering capacity of the stimulated saliva were found to be significantly lower in the AG group (p < 0.001 and p < 0.05, respectively). Conclusion. Although the prevalence of dental caries in the AG group was similar to that of the NAG group in this study, decreased quantity and buffering capacity of the stimulated saliva in the AG group may contribute to higher values of dental caries in asthmatic children in the future.